Day 2 Tue, September 27, 2016 2016
DOI: 10.2118/181386-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Flooding (LSF) in Sandstones at Pore Scale: Micro-Model Development and Investigation

Abstract: Low salinity waterflooding (LSF) is receiving increased interest as a promising method to improve oil recovery efficiency. Most of the literature agrees that on the Darcy scale, LSF can be regarded as a wettability modification process leading to a more water-wet state, although no general consensus on the microscopic mechanisms has been reached. While wettability alteration may be a valid causal mechanism also on the pore scale, it is currently unclear how oil that detaches from mineral surfaces within indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The possible role of crude oil and fluid–fluid interactions during LSWI in carbonate and sandstone reservoirs had been underestimated until microdispersion formation was introduced as the main responsible mechanism of LSWI . The microdispersion theory could support the extra oil recovery during LSWI regardless of rock type, which was a remarkable discovery for the oil and gas industry. , It was shown that microdispersions were water clusters surrounded with oil surface-active materials leading to wettability alteration through the detachment of surface-active materials from the rock surface; this work was also supported by other researchers. , Several studies have been published in the literature reporting the formation of water microdispersion as the main mechanism of LSWI irrespective of different terminologies. , Other mechanisms were also introduced to attribute the additional oil recovery during LSWI to the fluid–fluid interaction, such as interfacial viscoelasticity variations and osmotic effects . Alvarado et al suggested that either increasing the sulfate content or decreasing the salinity of injection water would lead to incremental oil recovery through increasing the interfacial viscoelasticity.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The possible role of crude oil and fluid–fluid interactions during LSWI in carbonate and sandstone reservoirs had been underestimated until microdispersion formation was introduced as the main responsible mechanism of LSWI . The microdispersion theory could support the extra oil recovery during LSWI regardless of rock type, which was a remarkable discovery for the oil and gas industry. , It was shown that microdispersions were water clusters surrounded with oil surface-active materials leading to wettability alteration through the detachment of surface-active materials from the rock surface; this work was also supported by other researchers. , Several studies have been published in the literature reporting the formation of water microdispersion as the main mechanism of LSWI irrespective of different terminologies. , Other mechanisms were also introduced to attribute the additional oil recovery during LSWI to the fluid–fluid interaction, such as interfacial viscoelasticity variations and osmotic effects . Alvarado et al suggested that either increasing the sulfate content or decreasing the salinity of injection water would lead to incremental oil recovery through increasing the interfacial viscoelasticity.…”
Section: Introductionmentioning
confidence: 59%
“…45,46 It was shown that microdispersions were water clusters surrounded with oil surface-active materials leading to wettability alteration through the detachment of surface-active materials from the rock surface; 47−49 this work was also supported by other researchers. 50,51 Several studies have been published in the literature reporting the formation of water microdispersion as the main mechanism of LSWI irrespective of different terminologies. 45,52−65 Other mechanisms were also introduced to attribute the additional oil recovery during LSWI to the fluid−fluid interaction, such as interfacial viscoelasticity variations 66 and osmotic effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still uncertain whether the mechanism has any quantitative significance compared to other low-salinity effects. Bartels et al (2010) reported from their micromodel experiments that osmosis was not a primary low-salinity mechanism [35].…”
Section: Current Research Resultsmentioning
confidence: 99%
“…Low-salinity brine was found to result in the preferential development of dynamic interfacial viscoelasticity, thereby suppressing pore-level snap-off events. Bartels et al (2016) and Bartels et al (2017) used clay-coated micromodels to investigate the low-salinity effect and its dependence on crude oil properties, presence of clay particles and aging. Amirian et al (2017) utilized the approach, proposed by Song and Kovscek (2015) to deposit clay particles into micromodels and visualized the micro-mechanism of displacement under LSW injection.…”
Section: Hydrocarbon Recoverymentioning
confidence: 99%